Diagnóstico sobre el manejo y disposición de los residuos sólidos de construcción y demolición en Colombia (2023)
The management and final disposal of solid construction and demolition waste in Colombia has been a topic of concern in recent years due to the growing generation of this waste and its environmental and social impact. Recent studies reveal that the management of this waste still faces several challenges, such as the lack of adequate infrastructure, the absence of clear regulations, and the lack of environmental awareness on the part of the governments and actors involved. In Colombia, millions of tons of solid construction and demolition waste are generated per year, of which a very low percentage is managed properly. Most waste is deposited in illegal landfills, causing soil, air and water pollution. A lack of clear and specific regulations on the management of construction and demolition waste can be identified, which has led to not responsibility on the part of the actors involved, the lack of incentives for the reuse and recycling of this waste should also be highlighted, which could significantly reduce its environmental impact. To address these challenges, it is recommended the implementation of clearer and more specific policies, investment in infrastructure for adequate waste management, and the promotion of environmental awareness, responsibility on the part of the actors involved. In addition, research into innovative technologies to reuse construction and demolition waste should be encouraged to reduce its environmental impact and create sustainable economic opportunities.